Problems of Teachers In Distance Learning on Thematic Learning the Madrasah Ibtidaiyah - Dini Urwatul Wustqo; Suryadi Suryadi (EDUCARE: Journal of Primary Education, 2022)
Distance learning in thematic learning Class IV at MI Nurul Ulum. Distance learning is learning without doing face-to-face, learning through google classroom, home study, zoom, video, and more. The purpose of this study is to analyze the problems of teachers in distance learning on thematic learning in Madrasah ibtidaiyah. This research method uses a qualitative approach and type of Field Research. Data collection techniques using observation, interviews, and documentation. While data analysis using Miles, Huberman, and Saldana analysis models of data condensation, data presentation, and conclusion drawing. Then wet, the data using triangulation methods and triangulation sources. The results of this study showed: 1.) The problems of teachers in distance learning in thematic learning in Madrasah ibtidaiyah Nuru Ulum are: the absence of supporting facilities, the absence of internet quota, and the absence of an internet network. 2) efforts to overcome the problems of teachers in distance learning in thematic learning Class IV MI Nurul Ulum, namely: teachers by going directly to the homes of students and students learning in groups by utilizing wifi at-home learners. Pembelajaran jarak jauh pada pembelajaran tematik kelas IV di MI Nurul Ulum. Pembelajaran jarak jauh adalah pembelajaran yang dilakukan tanpa melakukan tatap muka, pembelajaran melalui google classroom, rumah belajar, zoom, video dan lainnya. Tujuan dari penelitian ini untuk menganalisis problematika guru dalam pembelajaran jarak jauh Pada Pembelajaran Tematik di madrasah ibtidaiyah. Metode penelitian ini menggunakan pendekatan kualitatif dan jenis penelitian lapangan. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Sedangkan analisis data menggunakan model analisis Miles, Huberman, dan Saldana kondensasi data, penyajian data dan penarikan kesimpulan. Kemudian kebasahan data menggunakan triangulasi metode dan triangulasi sumber. Hasil penelitian ini menunjukkan: 1.) Problematika guru dalam pembelajaran jarak jauh pada pembelajaran tematik di madrasah ibtidaiyah Nuru Ulum yaitu: ketiadaan fasilitas yang menunjang, ketiadaan kuota internet dan ketiadaan jaringan internet. 2) Upaya untuk upaya mengatasi problematika guru dalam pembelajaran jarak jauh dalam pembelajaran tematik kelas IV MI Nurul Ulum yaitu: guru dengan mendatangi langsung kerumah peserta didik dan siswa belajar berkelompok dengan memanfaatkan wifi dirumah peserta didik.